INTEGRATION OF NEW LITERACY CONCEPT IN THEMATIC SCIENCE TEACHING MATERIALS ON ENERGY UTILIZATION IN DAILY LIFE FOR GRADE VII STUDENTS - MIRI SUSANTI; Yurnetti Yurnetti; Asrizal Asrizal (Department of Science Education, 2020)
ABSTRACT Science learning material must be implemented in an integrated pattern according to curriculum 2013, but it still done separately such as chimistry biology and physics. To overcome this problem was developing of thematic science teaching materials integrated with new literacy. Where the concept that include to development research was: Using Energy in Daily Life. The goal of this study is to determine the validity and practicality of thematic science teaching materials. The instrument that used is questionnaire about the validity and practicality of product at administrated to Expert in field of this study. There are four Lecturers in field of Science Education and one from Physics Education. While practicality testing was carried out by 2 Science Teachers and 32 Junior High School Students. The technique of analysis data was descriptive statistical analysis. Based on the data analysis, the validity and practicality values ​​of the product with an average validity of 85.77 while the average practicality according to the teacher and students are 96.50 and 88.26. So it can be concluded that the thematic science teaching materials integrated in new literacy are valid and practical for grade VII junior high school students.